THREE STAGES IN THE HISTORY OF THE INSTITUTE - Lidia P. Chumakova (Высшее образование в России)
In the history of the Institute the author highlights three stages of its development and gives a description of each of them. For the first time in a single article it is provided a brief biographies of the heads of the university, their merits in the development of the educational institution were marked. It is shown that the current achievements of the Novosibirsk Law Institute (branch) of Tomsk State University have been created due to the selfless work of several generations of lawyers.